Sistem Penjaminan Mutu Internal Berbasis Website: (Studi Kasus : Institut Teknologi Dan Bisnis Bina Sriwijaya Palembang) - Muhammad Ridho Ardiansyah; Tri Suci Wulandari (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Currently, technology is also utilized for higher education, in ensuring optimal quality of higher education, it is necessary to have an effective and efficient internal quality assurance effort based on technology, to achieve quality and ensure the existence of a structured system in maintaining and improving the quality of the higher education. One important element in improving the quality of higher education is the internal quality assurance system. The Bina Sriwijaya Institute of Technology and Business Palembang as one of the private higher education institutions in South Sumatra, realizes the importance of building a strong quality culture as a foundation in realizing the vision of the institution. At The Bina Sriwijaya Institute of Technology and Business Palembang, the recapitulation of quality documents is still in the form of archived paper, questionnaires are still collected one by one by distributing questionnaire papers to respondents, namely students, lecturers and employees, there is no systematic SOP, and when the audit is carried out it is difficult to find documents so that it takes up time because it is not yet systematic. With this problem, researchers built a Website-Based Internal Quality Assurance System (Case Study: The Bina Sriwijaya Institute of Technology and Business Palembang). The development method used by the researcher is the prototype method, so that by using the prototype method it can help solve existing problems in order to realize the vision and mission of The Bina Sriwijaya Institute of Technology and Business Palembang